Optimum synthesis of oscillating slide actuators for mechatronic applications. Issue 2 (25th September 2017) - Simionescu, P.A.
Graphical abstract: Abstract: The oscillating-slide inversion of the slider-crank mechanism, commonly symbolized RP RR, is widely used to convert the displacement of an input linear motor (either electric, hydraulic or pneumatic), into the swing motion of a rocker. This paper discusses the optimum kinematic synthesis of the centric RP RR mechanisms for prescribed limit positions, while simultaneously satisfying either (i) minimum deviation from 90° of its transmission angle, (ii) maximum mechanical advantage, or (iii) linear correlation between the input- and output-link motions. To assist practicing engineers, step-by-step design procedures, together with performance charts and parametric design charts are also provided in the paper.